2017
DOI: 10.1002/eco.1923
|View full text |Cite
|
Sign up to set email alerts
|

Beaver‐mediated water table dynamics in a Rocky Mountain fen

Abstract: Beaver dams are known to raise water tables in mineral soil environments, but very little is known about their impact in wetlands, such as peatlands. Peatlands tend to have shallow water tables, and the position and tendency of the water table to fluctuate (i.e., stability) is a factor controlling the system's ability to store carbon and water. Many peatland environments, especially fens, offer ideal habitat for beaver, and the potential for beaver dams to influence this link by manipulating water tables requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 55 publications
(95 reference statements)
0
29
0
Order By: Relevance
“…At the end of data set, water tables at W4 and W7 were 0.45 and 0.58 m, respectively, lower than water tables at W61 and W62. Of note, wells 61 and 62 were within the 150‐m zone of influence of a beaver dam; water tables are elevated 13 cm on average when in this zone of influence (Karran et al, ). From 28 June to the beginning of August, well 4 and 7 water tables declined at an average rate of 13 mm/day, and well 62 and 62 water tables declined at a rate of 5 mm/day.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…At the end of data set, water tables at W4 and W7 were 0.45 and 0.58 m, respectively, lower than water tables at W61 and W62. Of note, wells 61 and 62 were within the 150‐m zone of influence of a beaver dam; water tables are elevated 13 cm on average when in this zone of influence (Karran et al, ). From 28 June to the beginning of August, well 4 and 7 water tables declined at an average rate of 13 mm/day, and well 62 and 62 water tables declined at a rate of 5 mm/day.…”
Section: Resultsmentioning
confidence: 99%
“…Water from the beaver ponds may have bypassed the dams by way of throughflow or escaping through weakened areas of dam construction (Westbrook, Cooper, & Baker, ; Woo & Waddington, ). Sibbald fen usually has many beaver ponds (Karran et al, ; Morrison et al, ), and the few present during the study likely influenced the observed gradual return of streamflow after rainstorms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations